Research of Quality Indicators of Fur Plates from a Fur Flap - et. al., Nigora Dzhurakhonovna ERGASHEVA , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Much attention is paid to the issues of waste-free use of the area of skins of fur semi-finished products of various types. The share of costs for fur and leather semi-finished products in the cost of fur and leather products reaches 80–90%. Therefore, their economical use plays a very significant role in reducing the cost of products. Increasing the utilization rate of fur semi-finished products and natural leather materials due to the maximum use of the flap and low-grade raw materials plays an important role.The use of an expensive semi-finished product and manufacturing methods, a large variability of physical and mechanical properties, determined by the natural and biological characteristics of animals, require comprehensive research to develop and form the principles of domestic design of fur products.